Kontruksi Praktek Pendidikan Keteladanan dan Nasehat Dalam Alquran - Kapitri, Neneng; Samsurizal, Samsurizal; Rahmita, Rahmita (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2023)
In the modern era, the Muslim world faces a new context that did not exist in previous eras. Modernization plays an important role in decisive events, both globally and in Muslim society, one of which is the study of Sufism. This is very interesting both in the context of Islamic teachings and in the context of the historical development of Islamic civilization. Many new ideas, both in terms of ontology, epistemology, and value theory, have flowed into the development of Sufism research. Can improve the practice of worship, morality, and spiritual matters. The fact is that Sufism cannot be separated from the framework of religious experience which is based on the Koran and Sunnah. This is what is called modern Sufism, a Sufism that brings progress, a spirit of monotheism, and is far from shirk, heresy, and superstition. Sufism is only a tool, not a goal. The essence of Sufism is an effort aimed at improving and purifying the mind, which can inspire thoughts in the form of increasing social sensitivity among Sufis. When science began to develop, followed by modern technology, in the Western world today it lost its human meaning, life was hampered by individualism, and love and friendship faded. People are preoccupied with competition and the benchmark of success lies in material things, they have been shunned, valued spiritually, and with God, so it is not surprising that lately Sufism has taken hold at the head of the spread. Sufism is a way to stay away from materialistic and worldly things because it contains a fairly rich and deep spiritual conception of Islam.